Strengths and weaknesses of NGOs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Reluctant partners? non-governmental organizations, the state and sustainable agricultural development, John Farrington and Anthony Bebbington with Kate Wellard and David J Lewis. Non-governmental organizations and the state in Asia: rethinking roles in